Investigating the momentary association between maternal support and children's fruit and vegetable consumption using ecological momentary assessment. (1st July 2020) - Do, Bridgette; Yang, Chih-Hsiang; Lopez, Nanette V.; Mason, Tyler B.; Margolin, Gayla; Dunton, Genevieve F.
Abstract: Despite compelling evidence that fruit and vegetable (F/V) consumption can reduce the risk of obesity and chronic disease, most children fail to meet the daily recommendations for dietary consumption. Theoretical models and empirical findings suggest that parents play a key role in guiding children's overall dietary behaviors. To extend previous findings, the current study utilized ecological momentary assessment (EMA) on smartphones to assess the within-subject and between-subject effects of maternal support (i.e., encouragement, preparation) of F/V on their child's F/V consumption. Mother-child dyads (n = 191) completed six semi-annual 7-day waves of EMA surveys. EMA assessed mothers' past 2-h support for F/V and children's F/V consumption. At the within-subject level, greater maternal encouragement for F/Vs (OR = 2.41) and maternal preparation of F/Vs (OR = 1.43) than usual were associated with increased odds of their child eating F/V during the same 2-h window. At the between-subject level, greater maternal preparation of F/V (OR = 5.99), compared to other mothers, was associated with increased odds of their child eating F/V. Children with lower BMI (vs. higher BMI) were more likely to consume F/Vs when their mothers encouraged them to eat F/V (OR = 0.74). These findings suggest that maternal support may have a strong and immediate effect on children's F/V consumption. Theoretical models on behavior change should consider how explanatory factors, such as parental support, may vary at the momentary level. Boosting maternal support at the momentary level may be a critical component of future mobile-based interventions to address childhood obesity.